Early contraceptive implant removal and associated factors among women attending public family planning clinics, Mbarara City, Southwestern Uganda: a crosssectional study - Rwebazibwa, Joseph; Migisha, Richard; Munaru, Gideon; Byamukama, Onesmus; Abesiga, Lenard; Mugyenyi, Godfrey R.; Kalyebara, Paul Kato; Tibaijuka, Leevan; Ngonzi, Joseph; Kajabwangu, Rogers; Turanzomwe, Stuart; Mohammed, Fadumo; et al. (Contraception and Reproductive Medicine, 2024)
Background: Early implant removal not only results in method wastage and strains healthcare resources but also exposes women to the risk of unplanned pregnancies and associated complications if an alternative contraceptive is not promptly adopted. Studies have demonstrated that prevalence and factors associated with contraceptive use vary across different cultures and regions even within Uganda. We determined the prevalence and associated factors of early implant removal, among women attending public family planning clinics in Mbarara City, southwestern Uganda. Methods: We conducted a cross-sectional study from April to July 2023 at four public family planning clinics in Mbarara City. We consecutively enrolled women and administered a questionnaire to obtain data on demographic, and medical characteristics. We defined early removal as implant discontinuation within a period < 2 years. We excluded women who did not have a written record of the date of insertion of the contraceptive implants. We used modified Poisson regression analysis to determine factors associated with early implant removal. Results: We enrolled 406 women, with a mean age of 29 ± 6 years. The prevalence of early contraceptive implant removal was 53% (n = 210; 95%, CI: 48-58%). Factors associated with early implant removal were experiencing side effects (adjusted prevalence ratio [aPR] = 1.63, 95% CI: 1.20–2.21), inserting an implant to achieve career goals (aPR = 1.88, 95% CI: 1.26–2.81) and intending to use the implant for < 24 months (aPR = 1.36, 95% CI: 1.11–1.66). Conclusion: Approximately half of the surveyed women removed their contraceptive implant early. Women who experienced side effects, chose an implant due to career obligations and those whose intended implant use was < 2 years were more likely to have an early contraceptive implant removal compared to their counterparts. We recommend strengthening of pre- and post- insertion counselling to address concerns among those who may experience side-effects. Women who intend to use implants for < 2 years and those who have career obligations should be encouraged to use short-acting methods as an option.
Keywords: Contraception; Contraceptive implants; Contraceptive removal; Family planning; Southwestern Uganda